2021
DOI: 10.5603/fm.a2020.0093
|View full text |Cite
|
Sign up to set email alerts
|

Agenesis of the coeliac trunk: a case report and review of the literature

Abstract: Vascular anatomical variations of the abdomen are very common. Awareness of these variations is of paramount importance in clinical practice mainly in achieving best results in minimal invasive or surgical vascular procedures. From surgical point of view, the preoperative knowledge of vascular anatomy and the relations to the surrounding structures and tissues aims to minimize inadvertent complications. Agenesis of the celiac trunk is one of the rare anatomical variations of the abdominal aorta. Limited number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Jedan deo osoba sa nedostatkom celijačnog stabla se otkrije slučajno, izvan ciljanih istraživanja, prilikom dijagnostike savremenim radiološkim tehnikama. Tako su Karamanidi i saradnici [34], u svom prikazu slučaja, opisali šezdesetdevetogodišnju pacijentkinju, a Van den Broek i saradnici [8] jednog pacijenta sa Juingovim sarkomom, kod kojih je ova varijacija primećena prilikom pregleda abdomena kompjuterizovanom tomografijom. I u našem radu je nedostatak celijačnog stabla zapravo bio slučajni nalaz, uočen tokom pregleda abdomena magnetnom rezonancom.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Jedan deo osoba sa nedostatkom celijačnog stabla se otkrije slučajno, izvan ciljanih istraživanja, prilikom dijagnostike savremenim radiološkim tehnikama. Tako su Karamanidi i saradnici [34], u svom prikazu slučaja, opisali šezdesetdevetogodišnju pacijentkinju, a Van den Broek i saradnici [8] jednog pacijenta sa Juingovim sarkomom, kod kojih je ova varijacija primećena prilikom pregleda abdomena kompjuterizovanom tomografijom. I u našem radu je nedostatak celijačnog stabla zapravo bio slučajni nalaz, uočen tokom pregleda abdomena magnetnom rezonancom.…”
Section: Discussionunclassified
“…A certain number of persons with an absent celiac trunk is discovered accidentally, outside targeted studies, during the application of modern radiological diagnostic techniques. Thus, in their case study, Karamanidi et al [34] described a sixty-nine-year-old female patient, while Van den Broecke et al [8] described a patient with Ewing sarcoma, in whom this variation was observed upon CT examination of the abdomen. In our study, the absence of the celiac trunk was, in fact, also an incidental finding, observed during MRI examination of the abdomen.…”
Section: Diskusijamentioning
confidence: 99%
“…In some individuals, the celiac trunk is completely absent [ 4 ]. Therefore, anatomical variants of the celiac trunk branches may be the result of anomalous embryogenesis of the primitive segmental splanchnic arteries [ 7 ].…”
Section: Introductionmentioning
confidence: 99%